Characterization of Bacterial Exopolysaccharides Produced from Different Fruit-Based Solid Media - Marie Guérin; Cyrielle Garcia; Christine Robert-Da Silva; Joël Couprie; Fabienne Remize (Fermentation, 2023)
Bacterial exopolysaccharides (EPSs) share their compositional and structural features with plant dietary fibers. Therefore, analysis of bacterial EPSs produced during fermentation of fruit or vegetables interferes with that of plant fibers. To get rid of this effect, bacteria were grown on a solid medium containing fruit juice or purée and EPSs were recovered in a quantitative dependent manner and were quantified with the phenol-sulfuric acid colorimetric method. The protocol was assayed both on MRS medium and fruit-based media, with three bacterial strains from two species, Leuconostoc pseudomesenteroides 56 and Weissella cibaria 21 and 64. With that method, differences in EPS production levels were shown according to the strain and cultivation conditions, such as sucrose content and pH. Complementary analysis with NMR indicated that glucose and sucrose were partly recovered with EPSs, pointing out the requirement for a further purification step. It also showed that EPSs’ ramified structure differed according to the strain and the fruit used in the medium. This method for EPS recovery is helpful to select strains and to pilot EPS production during lactic fermentation of fruit or vegetable foods.